Metode Penerjemahan Kritis Manuskrip Klasik Jawa: Upaya Penyediaan Bahan Penelitian Lintas Ilmu - Mulyana, Mulyana (Kementerian Sekretariat Negara Republik Indonesia, 2022)
Javanese classical manuscripts provide a variety of important scientific materials that can be researched. Research that examines Javanese classical manuscripts requires the ability to read characters and a goodunderstanding of Javanese language. The purpose of the study is to provide valuable research materials (data) from Javanese classical texts for interdisciplinary research. The research approach used is descriptivequalitative. The research subjects were three Javanese classical manuscripts entitled: (1) Suluk Kumandaka, (2) Serat Darma Laksita, and (3) Serat Kudhup Sari. The object of study is to analyze the text (sentences) of the manuscript which contains certain scientific values. Data were collected by reading and note-taking techniques.Subsequently, the data validated by repeated and in-depth reading. Data analysis was carried out using descriptive-qualitative, through critical translation techniques and stage, namely: text critical, language critical,and substance critical. Furthermore, the study of the substance (content) of the manuscript revealed by the method of content analysis. The three classical Javanese manuscripts studied contain: moral values, Islamicreligious values, and educational values. The results of the data analysis show that critical translation work is able to provide mature materials (data) for cross-disciplinary research. Keywords : critical translation, Javanese classical manuscripts, cross-disciplinary research